Struktur Naratif Cerita Lokal Gunung Kidul “Petilasan Watu Tumpeng” - Mulatsih, Maria Vincentia Eka; Manggala, Simon Arsa; Nirwinastu, Diksita Galuh (Ideas Publishing, 2024)
The process of transferring values and culture contained in local stories needs to be passed on to the younger generation, one way is by documenting local stories. Related to this, this article is one form of documentation of a local story entitled Watu Tumpeng from Bohol village, Gunung Kidul. The method for completing this story is in accordance with the methodology proposed by Appell (Appell, 2014) and the macrostructure elements of the story are identified based on Labov's narrative elements. The final result is a story that is better structured based on Labov's narrative structure including abstract, orientation, complicating actions, evaluation, results or resolution and coda. This study enriches the documentation of folklore, especially in the Gunung Kidul area.